2014
DOI: 10.1111/flan.12118
|View full text |Cite
|
Sign up to set email alerts
|

It Takes a Department! A Study of the Culture of Proficiency in Three Successful Foreign Language Teacher Education Programs

Abstract: The aim of this study was to investigate the contexts and practices of three undergraduate foreign language teacher education programs identified by ACTFL/Language Testing International and reported by Glisan, Swender, and Surface (2013) as having a high success rate in propelling their graduates into the Advanced proficiency level on the ACTFL scale. Data were collected during interviews with faculty and students at each of the three campuses. The results revealed a number of common practices among the progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
2
15
0
2
Order By: Relevance
“…Consequently, we would argue that the most important implication here is the responsibility that FL teacher preparation programs have in differentiating and tailoring the completion of particular courses and field experiences to the specific needs of teacher candidates—e.g., strengthening oral proficiency, developing knowledge of language, expanding teaching skills—so that candidates eventually excel in all areas rather than compensating for their deficiencies upon entering the classroom as licensed teachers. In our view, Kissau and Algozzine would have made a significant contribution had they focused their implications on the program model that they suggested in Figure 2 (p. 130), particularly since it includes several components (e.g., a midpoint OPI assessment) that have been identified in earlier research examining effective models of FL preparation that indeed represent the profession's gold standard (Brooks & Darhower, ; Huhn, ).…”
Section: Conclusion: the Real Implication For Teacher Preparation Promentioning
confidence: 97%
See 1 more Smart Citation
“…Consequently, we would argue that the most important implication here is the responsibility that FL teacher preparation programs have in differentiating and tailoring the completion of particular courses and field experiences to the specific needs of teacher candidates—e.g., strengthening oral proficiency, developing knowledge of language, expanding teaching skills—so that candidates eventually excel in all areas rather than compensating for their deficiencies upon entering the classroom as licensed teachers. In our view, Kissau and Algozzine would have made a significant contribution had they focused their implications on the program model that they suggested in Figure 2 (p. 130), particularly since it includes several components (e.g., a midpoint OPI assessment) that have been identified in earlier research examining effective models of FL preparation that indeed represent the profession's gold standard (Brooks & Darhower, ; Huhn, ).…”
Section: Conclusion: the Real Implication For Teacher Preparation Promentioning
confidence: 97%
“…In addition, she also admitted not having the confidence to teach upper‐level courses as a result of her proficiency level. Research has shown that successful FL teacher preparation programs in collaboration with modern language departments intentionally create a “culture of oral proficiency” in which candidates learn how proficiency develops, receive consistent feedback on their speaking ability, and are afforded opportunities to improve their proficiency outside of class (Brooks & Darhower, ; Huhn, ). Of course, a culture of oral proficiency in a language department also requires that the faculty understand the developmental trajectory of language learners, what proficiency in a foreign language means, and how to support students toward programmatic proficiency goals.…”
Section: Content Knowledge Of Fl Teachers: Broaden or Compensate?mentioning
confidence: 99%
“…Desempenho e proficiência são os pilares deste pressuposto teórico. Enquanto o desempenho é a habilidade ensaiada em sala de aula da língua-alvo, a proficiência é a habilidade de uso espontâneo da língua-alvo em contextos reais (BROWN & ABEYWICKRAMA, 2010). A prática das funções da linguagem, estruturas e vocabulário são geralmente dispostas em uma variedade de tarefas relacionadas a um currículo e podem ser avaliadas como conhecimento memorizado.…”
Section: Debate Acadêmicounclassified
“…Cada categoria é determinada por uma cor e subdividida em outras 3 subcategorias de proficiência. Vale lembrar que o conceito de proficiência linguística adotado aqui é a capacidade de um indivíduo de usar uma linguagem culturalmente apropriada para se comunicar de maneira espontânea; já o desempenho linguístico é o treino para a aquisição da aptidão da comunicação em contextos culturalmente ricos e não-ensaiados (BROOKS & DARHOWER, 2014).…”
Section: Debate Acadêmicounclassified
“…Presently, the fifth phase of the initiative is underway. Research from the initiative includes studies about the attainment of the oral proficiency standard (Brooks & Darhower, 2014), high-leverage teaching practices (e.g., Kearney, 2015), the world language edTPA (Hildebrandt & Swanson, 2014), communities of practice (J. Terantino), Chinese immersion (C. L€ u), and content-based instruction (J. Martel), to name just a few projects.…”
mentioning
confidence: 99%